Pharmacological Properties of 2,4,6-Trihydroxy-3-Geranyl Acetophenone and the Underlying Signaling Pathways: Progress and Prospects - Chan, Yee Han; Liew, Kong Yen; Tan, Ji Wei; Shaari, Khozirah; Israf, Daud Ahmad; Tham, Chau Ling (Frontiers in Pharmacology, 2021)
2,4,6-Trihydroxy-3-geranyl acetophenone (tHGA) is a bioactive phloroglucinol compound found in Melicope pteleifolia (Champ. ex Benth.) T.G.Hartley, a medicinal plant vernacularly known as ‘tenggek burung’. A variety of phytochemicals have been isolated from different parts of the plant including leaves, stems and roots by using several extraction methods. Specifically, tHGA, a drug-like compound containing phloroglucinol structural core with acyl and geranyl group, had been identified in the methanolic extract of the young leaves. Due to its high nutritional and medicinal values, tHGA has been extensively studied in different experimental models. These studies have successfully discovered various interesting pharmacological properties of tHGA such as anti-inflammatory, endothelial and epithelial barrier protective, anti-asthma, anti-allergic, and anti-cancer. More in-depth investigations later found that these effects were attributable to the modulatory actions exerted by tHGA on various molecular targets. Despite these findings, the association between the mechanisms and signaling pathways underlying each pharmacological activity remains largely unknown. Also, little is known about the medicinal potentials of tHGA as a drug lead in the current pharmaceutical industry. Therefore, this mini review aims to summarize and relate the pharmacological effects of tHGA in terms of their respective mechanisms of action and signaling pathways in order to present a perspective into the overall modulatory actions exerted by tHGA. Besides that, this mini review will also pinpoint the unexplored potentials of this compound and provide some valuable insights into the potential applications of tHGA which may serve as a guide for the development of modern medication in the future.